Decentralization and collaborative disaster governance - BAE, Yooil (Institutional Knowledge at Singapore Management University, 2015)
Decentralized disaster governance has been gaining much attention with the rising global urbanization rate and the complex nature of the disasters occurring in densely urbanized areas today. This paper studies the case of South Korea, a highly urbanized country with relatively recent decentralization reforms, in order to analyze the evolution of its disaster management system and to draw out implications from its experience. Specifically, it traces the national-level institutional changes in its disaster management, and then closely examines a hydrofluoric gas leakage in the industrial city of Gumi. The finding is that South Korea simultaneously carried out both centralization and decentralization of disaster management, which are not contradictory but rather complementary. Nevertheless, while the country successfully set up an integrated and comprehensive national-level management system, from which disaster governance can successfully be decentralized to localities, it still requires much more developed and consolidated multilevel (vertical) and broader (horizontal) collaboration, which are the preconditions for decentralized disaster governance.